2016
DOI: 10.1007/s00442-016-3735-x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal dynamics with compensatory effects regulate populations of tropical forest marsupials: a 16-year study

Abstract: The conditions that a population experiences during one season can affect the strength of density dependence in the following season. In the tropics, many populations face their biggest challenges in the dry season due to limited food and cold-dry conditions. Seasonal environmental changes can be especially problematic for small, short-lived, seasonally breeding endotherms. To investigate the effects of seasonality on population dynamics, we studied five marsupial species in the Brazilian Atlantic Forest, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Following Ferreira et al (2016), we modeled population growth rate in a given year ( λ t ) as a function of past population sizes in current ( t ) and previous ( t -1 … t - i ) years. The linear autoregressive model was:where α t … α t - i are the slopes of the relationship between λ t and population size in a given year ( t … t - i ) and represent the strength of density dependence, and ε t represents the process noise.…”
Section: Methodsmentioning
confidence: 99%
“…Following Ferreira et al (2016), we modeled population growth rate in a given year ( λ t ) as a function of past population sizes in current ( t ) and previous ( t -1 … t - i ) years. The linear autoregressive model was:where α t … α t - i are the slopes of the relationship between λ t and population size in a given year ( t … t - i ) and represent the strength of density dependence, and ε t represents the process noise.…”
Section: Methodsmentioning
confidence: 99%
“…The need to identify the period of the annual cycle that is driving population declines is particularly pertinent to migratory species whose seasonal habitats are often separated by vast geographic distances and whose populations have experienced ongoing global declines (Wilcove & Wikelski 2008;Young et al 2016;Ceballos et al 2017). Several recent examples have demonstrated the insights gained from integrating information across the annual cycle to understand how changes in the environment drive population dynamics, both in the wild (Norris & Marra 2006;Luis et al 2010;Ferreira et al 2016;Woodworth et al 2017;Sutton et al 2019) and in experimental populations (Betini et al 2013a(Betini et al , 2014(Betini et al , 2017. Knowledge of when and where populations are limited has important implications for the targeting of conservation efforts and funding (Sheehy et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The lack of density dependence on M. nudicaudatus movements enlightens the mechanism of population regulation. Previous studies in the study area have shown that M. nudicaudatus is regulated by a direct negative feedback (Ferreira et al 2016a), especially in the dry season (Ferreira et al 2016b), and suggested intraspecific competition for food resources and/or space as the main regulatory mechanisms. Space is not a limiting factor for this population, reinforcing that most of the intraspecific competition takes place during the dry season.…”
Section: Modelmentioning
confidence: 84%